Business model development of forest-based ecotourism in perum perhutani ( a case study in pulo merah banyuwangi, east java) - Sianturi, Veronika; Hamsal, Muhammad (The Indonesian Journal of Business Administration, 2018)
Abstract. Managing about 2,4 million hectare production and protection forests in Java and Madura island, Perum Perhutani at least have 700 ecotourism objects in the form of forest, beach, waterfall, lake, crater and cave. Since the company has not set this business seriously, its contribution to the company’s revenue is still low.   This study aimed to evaluate the performance of one ecotourism spot in  Perhutani named Pulo Merah, which is located within its forest area in Banyuwangi East Java. According to number of its visitor, Pulo Merah is potential to be developed as sources of income for the company. In addition, it is located near the Sukamade beach, one of The Triangle Diamond which is set as main tourist destination by local government of Banyuwangi. The IPA (importance-performance analysis) was conducted to assess performance of Pulo Merah and its development priority through spreading questionaire to visitors. The research reveal that the main priority of improvement for Pulo Merah are road access to location, increase of electricity and telecommunication network, improvement of beach area cleanliness, improvement of public toilets and washing facilities quality, addition number of trash can and addition of warning boards of danger, and warning boards not to exploit plants and animals in the beach areas. Keywords : banyuwangi, ecotourism,  importance-performance analysis, perhutani, pulo merah